Kajian Hukum Terhadap Tindak Pidana Mengedarkan Obat Yang Tidak Memiliki Izin Edar (Studi Putusan Nomor : 1131/Pid.Sus/2018/PN.Mdn) - Anggi Nadya Nasution; Muazzul Muazzul; Wessy Trisna (Universitas Medan Area, 2020)
Crimes in the pharmaceutical field, which are related to drug distribution without circulation authorization, have occurred in many regions in Indonesia. The rise of the circulation of illegal drugs proves that Indonesia's defense is still weak from the invasion of things that endanger the community. This type of research is normative research and the nature of the study used is analytical descriptive. Data will be analyzed by qualitative methods. Based on data analysis conducted Legal arrangements regarding drug distribution licenses are in the Regulation of the Head of the Republic of Indonesia Drug and Food Supervisory Agency Number HK.00.05.1.23.3516 Concerning Circulars of Drug Products, Traditional Medicines, Cosmetics, Food Supplements, and Food Sourced, Containing , Of Specific Ingredients and Or Containing Alcohol, Law No. 8 of 1999 concerning Consumer Protection, Regulation of the Head of the Republic of Indonesia Drug and Food Supervisory Agency Number 24 of 2017 concerning Criteria and procedures for drug registration. Presidential Regulation (Perpres) Number: 80 of 2017 concerning the Food and Drug Supervisory Agency (BPOM).